1967
DOI: 10.2466/pr0.1967.21.2.681
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Verbal Conditioning and Meaning Conditioning

Abstract: Sunzmary.-Empirical relationships basic to two controversial hypotheses concerning the relationship of awareness to verbal operant conditioning and conditioning of meaning were studied. Experimental procedures integrated the two conditioning processes, systematically varied verbal reinforcements for Ss' verbal responses, measured awareness by questionnaire, and measured rated meaning of nonsense syllables, which had been associated with meaningful words. 15 Ss were assigned to each cf six experimental groups i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1968
1968
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 13 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…14478 This (David, 1967;Miller, 1967;and Mondy, 1968) supports the position that in VOC awareness precedes or occurs concurrently with response modification.…”
mentioning
confidence: 63%
“…14478 This (David, 1967;Miller, 1967;and Mondy, 1968) supports the position that in VOC awareness precedes or occurs concurrently with response modification.…”
mentioning
confidence: 63%
“…As with the issue of awareness in verbal conditioning studies, there are experiments (e.g., Insko & Oakes, 1966;Page, 1969) which reported that awareness is necessary for conditioning. On the other hand, there are other experiments which reported that awareness is not necessary for the classical conditioning of attitudes (Ertel, Oldenberg, Siry, & Vormfelde, 1969;Miller, 1966Miller, , 1967Minke & Stalling, 1970;Yavuz & Bousfield, 1959;Zanna et al, 1970). Those who consider awareness necessary tend to employ more extensive means of assessing awareness than those who consider awareness unnecessary.…”
Section: Delvedmentioning
confidence: 98%
“…Immediately after the experiment, each subject, tested individually, completed a questionnaire relating to her insight into the responsereinforcement process. The questionnaire was modelled on that used by Miller (1967). All those subjects who were aware of the connection between their behaviour and the experimenter's reinforcer were eliminated and replaced by others not so aware.…”
Section: Methodsmentioning
confidence: 99%